A Comprehensive Review of Traditional Indian Medicinal Plants For Therapeutic Implications In Alzheimer’s Disease And Its Associated Symptoms - Swapna Reddy KasiReddy; Ram Mohan Manda (The Bioscan, 2025)
Ayurvedic medicinal plants have been the single most productive source of leads for the development of drugs. In India, it is reported that traditional healers use nearly 2,500 plant species as regular sources of medicine for the treatment of various diseases. Alzheimer’s disease is the age associated progressive neurological disorder that causes brain cells to degenerate and finally dies. It is the most common form of dementia in people of 65 years and older with a continuous decline in thinking, behavioral and social skills that disrupts their ability to function independently. These disruptions cause nerve cells in the brain to stop working, lose connections with other nerve cells and finally die. As the disease progresses, a person will develop severe memory impairment and lose the ability to carry out everyday tasks. This disease is named after Dr. Alois Alzheimer in 1906 noticed changes in the brain tissue of woman who had died of an unusual mental illness. Her symptoms include memory loss, unpredictable behaviour, dehydration, malnutrition, infection & death. After she died, he examined her brain and found many amyloid plaques and tangled bundles of fibres. There is no treatment that cures the disease process in the brain, but some herbs may help to improve brain function, reduce its symptoms & improve quality of life and help the patients to some extent. The objective is to provide a systematic review of the ongoing evidence pertaining to the use of medicinal herbs in the treatment of AD and its associated symptoms.